Spillover effects of unconventional monetary policy in Asia and the Pacific - Maria Teresa Punzi; Pornpinun Chantapacdepong (Asian Development Bank Institute (ADBI), 2017)
We assess the evolution of spillover effects of unconventional monetary policies (UMPs) on Asia and the Pacific region, and evaluate the impact on and implications for the macroeconomy. We develop a Panel Vector Auto Regression model for Asia and the Pacific region for a period covering data from first quarter 2000 until first quarter 2015. We split the overall sample into two subsets: the Pre-Crisis (2000q1-2006q4) and Post-Crisis (2009q1-2015q1) samples. We identify UMP shocks with a shadow interest rate estimated by Krippner (2013). We find that Asia and the Pacific region has responded to the advanced economies' actions with accommodative monetary policy. Such lower interest rates were coupled with currency appreciation, asset price inflation, and strong movements in capital flows. Foreign investors have shifted their preferences for bonds in Asia and the Pacific. If prior to the Global Financial Crisis (GFC), the "global saving glut" hypothesis (i.e., Asian savings flight to the US) was one of the major effects resulting in booming US house prices, it is clear that a reversal effect has dominated the economy after the GFC: funds flight to Asia and the Pacific region putting pressure on asset prices, leading to financial vulnerability.
Keywords: E44; E52; F41; 330; spillover effects; unconventional monetary policy (UMP); Global Financial Crisis (GFC); funds flight; global savings glut